Vibration control and calculating inverse dynamics of the rigid-flexible two-link manipulator T-R - Khang, Nguyen Van; Dat, Dinh Cong (Vietnam Journal of Mechanics, 2022)
The dynamics and control of flexible link manipulators (FLMs) are increasing in industrial robotics research. In which the problem of inverse dynamics of the flexible link manipulators is a problem that has been studied little and has no general solution. In this paper, an approximation method is presented to calculate the reverse dynamics of the serial manipulators with rigid-flexible links. The linearization of the motion equations for a rigid-flexible translation and rotation two-link manipulator (manipulator T-R) is addressed. The vibration control and calculating inverse dynamics of a periodic rigid-flexible two-link manipulator T-R are studied. The Taguchi method is used for the design of gain values of the controller PD for the manipulator. The results of numerical simulation show the efficiency and usefulness of the proposed approximation method.